Research on Effective Electric-Mechanical Coupling Coefficient of Sandwich Type Piezoelectric Ultrasonic Transducer Using Bending Vibration Mode. (January 2015) - Zhang, Qiang; Shi, Shengjun; Chen, Weishan
An analytical model on electromechanical coupling coefficient and the length optimization of a bending piezoelectric ultrasonic transducer are proposed. The piezoelectric transducer consists of 8 PZT elements sandwiched between four thin electrodes, and the PZT elements are clamped by a screwed connection between fore beam and back beam. Firstly, bending vibration model of the piezoelectric transducer is built based on the Timoshenko beam theory. Secondly, the analytical model of effective electromechanical coupling coefficient is built based on the bending vibration model. Energy method and electromechanical equivalent circuit method are involved in the modelling process. To validate the analytical model, sandwich type piezoelectric transducer example in second order bending vibration mode is analysed. Effective electromechanical coupling coefficient of the transducer is optimized with simplex reflection technique, and the optimized ratio of length of the transducers is obtained. Finally, experimental prototypes of the sandwich type piezoelectric transducers are fabricated. Bending vibration mode and impedance of the experimental prototypes are tested, and electromechanical coupling coefficient is obtained according to the testing results. Results show that the analytical model is in good agreement with the experimental model.